1998
DOI: 10.1021/tx980170d
|View full text |Cite
|
Sign up to set email alerts
|

Stereochemistry of the Biotransformation of 1-Hexene and 2-Methyl-1-hexene with Rat Liver Microsomes and Purified P450s of Rats and Humans

Abstract: The epoxidation of 1-hexene (1a) and 2-methyl-1-hexene (1b), two hydrocarbons present in the ambient air as pollutants, is catalyzed by some human and rat P450 enzymes. The enantioselectivities of these processes, when the reactions were carried out using rat and human liver microsomal preparations, were modest and dependent on both P450 composition and substrate concentrations. Various P450 isoforms (rat P450 2B1 and human P450 2C10 and 2A6) catalyzed the double bond oxidation of 1a and 1b with different prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 25 publications
2
44
0
Order By: Relevance
“…It has been demonstrated that terminal double bonds may be oxidatised at the double bond to give the corresponding epoxide or, alternatively, at the allylic carbon to give the allylic alcohol, as was demonstrated with 1-hexene with rat and human P450s (Chiappe et al, 1998). The ratio of epoxidation over allylic oxidation, as measured with different P450 isoforms (CYP) is ≥1, indicating that epoxide formation is generally favoured (Chiappe et al, 1998).…”
Section: Figure Iii2 Metabolism Of Linear Unsaturated Carboxylic Acidmentioning
confidence: 96%
See 1 more Smart Citation
“…It has been demonstrated that terminal double bonds may be oxidatised at the double bond to give the corresponding epoxide or, alternatively, at the allylic carbon to give the allylic alcohol, as was demonstrated with 1-hexene with rat and human P450s (Chiappe et al, 1998). The ratio of epoxidation over allylic oxidation, as measured with different P450 isoforms (CYP) is ≥1, indicating that epoxide formation is generally favoured (Chiappe et al, 1998).…”
Section: Figure Iii2 Metabolism Of Linear Unsaturated Carboxylic Acidmentioning
confidence: 96%
“…The ratio of epoxidation over allylic oxidation, as measured with different P450 isoforms (CYP) is ≥1, indicating that epoxide formation is generally favoured (Chiappe et al, 1998). Theoretically these pathways could occur with the candidate substances 02.175,02.201,06.143,and 05.174].…”
Section: Figure Iii2 Metabolism Of Linear Unsaturated Carboxylic Acidmentioning
confidence: 99%
“…1-Alkenes are metabolised by P450 through both double bond oxidation to the corresponding epoxide and allylic oxidation (Chiappe et al, 1998). The rates of the two reactions measured with different P450 isoforms indicate that epoxide formation is generally favoured (Chiappe et al, 1998). Therefore, due to the similar position of the double bond, it cannot be ruled out that, in addition to the above mentioned metabolic pathways for ketones, the three candidate substances 07.201 and 07.239] may be, at least partially, biotransformed to an epoxide.…”
Section: Absorption Distribution Metabolism and Eliminationmentioning
confidence: 99%
“…The latter two reactions can be considered to be detoxications. 1-Alkenes are metabolised by P450, through both double bond oxidation to the corresponding epoxide and allylic oxidation (Chiappe et al, 1998). The rates of the two reactions measured with different P450 isoforms indicate that epoxide formation is generally favoured (Chiappe et al, 1998).…”
Section: Oxidation Of Terminal Double Bondsmentioning
confidence: 99%
“…Due to the large strain associated with the three membered ring structure epoxides easily react with nucleophilic sites of cellular macromolecules; conversely they are readily detoxified either spontaneously or by the action of epoxide hydrolase to diols or conjugated with reduced glutathione by glutathione-S-transferases. 1-Alkenes are metabolised by cytochrome P450, through double bond oxidation to the corresponding epoxide or alternatively allylic oxidation (Chiappe et al, 1998). The rates of the two reactions measured with different cytochrome P450 isoforms indicate that epoxide formation is generally favoured (Chiappe et al, 1998) and this may also apply in particular to the candidate substance dodec-1-ene ].…”
Section: Special Features Of Terminal Double Bond Oxidationmentioning
confidence: 99%